2012
DOI: 10.4132/koreanjpathol.2012.46.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Melanotic Oncocytic Metaplasia of the Nasopharynx: A Report of Three Cases and Review of the Literature

Abstract: Melanotic oncocytic metaplasia of the nasopharynx is a rare condition which is characterized by the presence of usually a small, brown to black colored pigmented lesion around the Eustachian tube opening. Although it is a benign lesion, it may be clinically misdiagnosed as malignant melanoma. Microscopically, melanotic oncocytic metaplasia is a combination of oncocytic metaplasia of the epithelium of the gland and melanin pigmentation in its cytoplasm. In our present study, we report three cases of melanotic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…The luminal lining cells contained not only melanin pigment (positive Fontana-Masson reaction) but also were immunoreactive for HMB-45, S-100 protein and melan A suggesting the production of melanin in these cells. Earlier reports of melanotic oncocytic metaplasia demonstrated melanin pigment in the seromucinous glands but the cells were HMB-45 negative [1]. This finding suggested that the melanin pigment may only have been phagocytized by the oncocytic epithelium rather than produced in these cells.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…The luminal lining cells contained not only melanin pigment (positive Fontana-Masson reaction) but also were immunoreactive for HMB-45, S-100 protein and melan A suggesting the production of melanin in these cells. Earlier reports of melanotic oncocytic metaplasia demonstrated melanin pigment in the seromucinous glands but the cells were HMB-45 negative [1]. This finding suggested that the melanin pigment may only have been phagocytized by the oncocytic epithelium rather than produced in these cells.…”
Section: Discussionmentioning
confidence: 54%
“…While two prior reports and our case had melan pigment within glandular epithelum, our case was positive for HMB-45 and melan A while the others were not. Additionally, the prior reports of melanotic oncocytic metaplasia occurred in Asian men [1,2] our patient was a Caucasian man. Finally, the seromucinous glands in our case did not show oncocytic change.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations